2022
DOI: 10.1007/s11845-022-02998-9
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii vaccine candidates: a concise review

Abstract: Toxoplasma gondii is an obligate intracellular parasite that causes toxoplasmosis. It has been shown that the severity of symptoms depends on the functioning of the host immune system. Although T. gondii infection typically does not lead to severe disease in healthy people and after infection, it induces a stable immunity, but it can contribute to severe and even lethal Toxoplasmosis in immunocompromised individuals (AIDS, bone marrow transplant and neoplasia). The antigens th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…Many of these proteins are involved in relevant strain specific host immunomodulatory functions, such as in the NFκB-IFN-γ axis or in the antigen presentation by MHC-I for a balanced host immune response required to achieve infection and to reduce CD8 + T cell recognition. These data, in addition to the fact that ROP antigens have long antigenic fragments and regions, support their selection as one of the strongest candidates as vaccine antigens [109][110][111]. Several ROP proteins (ROP2, 5,9,16,17,18,22,35) have been employed in vaccine strategies, mainly in DNA or protein vaccines against toxoplasmosis [23,[112][113][114].…”
Section: Ropsmentioning
confidence: 86%
See 1 more Smart Citation
“…Many of these proteins are involved in relevant strain specific host immunomodulatory functions, such as in the NFκB-IFN-γ axis or in the antigen presentation by MHC-I for a balanced host immune response required to achieve infection and to reduce CD8 + T cell recognition. These data, in addition to the fact that ROP antigens have long antigenic fragments and regions, support their selection as one of the strongest candidates as vaccine antigens [109][110][111]. Several ROP proteins (ROP2, 5,9,16,17,18,22,35) have been employed in vaccine strategies, mainly in DNA or protein vaccines against toxoplasmosis [23,[112][113][114].…”
Section: Ropsmentioning
confidence: 86%
“…We need to keep in mind that it is not the topic of this review to discuss the vaccine technology employed on each of those candidates. On the other hand, there are authors that have recently addressed that issue, such as Mamaghani et al, 2022 [111].…”
Section: Immune Response-based Candidates For Disease Managementmentioning
confidence: 99%
“…Toxoplasma gondii is thought to be one of the globally significant apicomplexan protozoa that are highly impacting people all over the world (Nazari et al 2018). Notably, the severity of toxoplasmosis is mainly affected by the host immune system integrity (Mamaghani et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that LNP technology can significantly boost the delivery of mRNA, thus providing intrinsic adjuvant activity and enhancing antigen expression. Many antigens have already been found to be potential vaccine candidates against T. gondii like TgSAGs, TgROPs, TgMICs, among others (Mamaghani et al, 2023). However, the efficacy of different vaccine candidates cannot be compared because they were administered via different routes, animal types, vaccination doses, and vaccine production processes, all of which affect immunization efficacy (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%